Men lining up to receive mail, Tagish, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Settlement between Tagish Lake and Marsh Lake. A post office was opened on August 20, 1897. Caption on image: "Receiving mail at Tagish Post - 1898"